Cascades of diabetes and hypertension care in Samoa: Identifying gaps in the diagnosis, treatment, and control continuum - a cross-sectional study - Lauren C. LaMonica; Stephen T. McGarvey; Anna C. Rivara; Chlöe A. Sweetman; Take Naseri; Muagatutia Sefuiva Reupena; Hemant Kadiamada; Erica Kocher; Alexa Rojas-Carroll; James P. DeLany; Nicola L. Hawley (Elsevier, 2022)
Summary: Background: Samoa is a Pacific Island country facing one of the highest burdens of non-communicable disease globally. Methods: In this study, we apply a cascade-of-care approach to understand gaps in the awareness, treatment, and control cascade of diabetes and hypertension in a cross-sectional, convenience sample of 703 young, high-risk Samoan adults (29.5-50.9 years). Findings: Non-communicable diseases were prevalent in the study sample: 19.5% (95% CI: 16.6%-22.7%) of participants had diabetes; 47.6% (95% CI: 43.7%-51.4%) presented with pre-diabetes or diabetes; 31.0% (95% CI: 27.5%-34.6%) had hypertension; and nearly 90% (95% CI: 86.7%-91.5%) had overweight or obesity. Among those with diabetes and hypertension, only 20.5% (95% CI: 13.9%-28.4%) and 11.8% (95% CI: 7.8%-16.9%) of participants were aware of their condition, respectively. Only 0.8% (95% CI: 0.0%-4.2%) of all participants with diabetes had achieved glycemic control; only 2.8% (95% CI: 1.1%-6.1%) of those with hypertension achieved control. Interpretation: We found a significant burden of diabetes and hypertension in Samoa, exceeding the recent prevalence estimates of other low- to middle-income countries by nearly two-fold. A severe unmet need in both detection and subsequent control and monitoring of these chronic conditions exists. Our results suggest that the initial diagnosis and surveillance stage in the cascade of care for chronic conditions should be a major focus of primary care efforts; national screening campaigns and programs that leverage village and district nurses to deliver community-based primary care may significantly impact gap closure in the NCD cascade. Funding: This study was supported by the U.S. National Institutes of Health R01HL140570 (PIs: McGarvey and DeLany); AR was supported by NIH FIC D43TW010540; HK and AR-C were supported by the Minority Health and Health Disparities International Research Training (MHIRT) Program at Brown University, NIH Grant # 5T37MD008655.